Serum Calprotectin: An Antimicrobial Peptide as a New Marker For the Diagnosis of Sepsis in Very Low Birth Weight Newborns - Gianluca Terrin; Annalisa Passariello; Francesco Manguso; Gennaro Salvia; Luciano Rapacciuolo; Francesco Messina; Francesco Raimondi; Roberto Berni Canani (Clinical and Developmental Immunology)
To determine the diagnostic utility of serum calprotectin, a mediator of innate immune response against infections, we performed a multicenter study involving newborns with a birth weight <1500 g and a postnatal age >72 hours of life. The diagnostic accuracy of serum calprotectin was compared with that of the most commonly used markers of neonatal sepsis (white blood cell count, immature-to-total-neutrophil ratio, platelet count, and C-reactive protein). We found that the serum calprotectin concentration was significantly higher (P<.001) in 62 newborns with confirmed sepsis (3.1±1.0 μg/mL) than in either 29 noninfected subjects (1.1±0.3 μg/ml) or 110 healthy controls (0.91±0.58 μg/ml). The diagnostic accuracy of serum calprotectin was greater (sensitivity 89%, specificity 96%) than that of the traditional markers of sepsis. In conclusion, serum calprotectin is an accurate marker of sepsis in very low birth weight newborns.